Quantifying Alumina Nanoparticle Dispersion in Hybrid Carbon Fiber Composites Using Photoluminescent Spectroscopy. Issue 2 (February 2017) - Hanhan, Imad; Selimov, Alex; Carolan, Declan; Taylor, Ambrose C.; Raghavan, Seetha
Composites modified with nanoparticles are of interest to many researchers due to the large surface-area-to-volume ratio of nano-scale fillers. One challenge with nanoscale materials that has received significant attention is the dispersion of nanoparticles in a matrix material. A random distribution of particles often ensures good material properties, especially as it relates to the thermal and mechanical performance of composites. Typical methods to quantify particle dispersion in a matrix material include optical, scanning electron, and transmission electron microscopy. These utilize images and a variety of analysis methods to describe particle dispersion. This work describes how photoluminescent spectroscopy can serve as an additional technique capable of quickly and comprehensively quantifying particle dispersion of photoluminescent particles in a hybrid composite. High resolution 2D photoluminescent maps were conducted on the front and back surfaces of a hybrid carbon fiber reinforced polymer containing varying contents of alumina nanoparticles. The photoluminescent maps were analyzed for the intensity of the alumina R1 fluorescence peak, and therefore yielded alumina particle dispersion based on changes in intensity from the embedded nanoparticles. A method for quantifying particle sedimentation is also proposed that compares the photoluminescent data of the front and back surfaces of each hybrid composite and assigns a single numerical value to the degree of sedimentation in each specimen. The methods described in this work have the potential to aid in the manufacturing processes of hybrid composites by providing on-site quality control options, capable of quickly and noninvasively providing feedback on nanoparticle dispersion and sedimentation.